TorsinA hypofunction causes abnormal twisting movements and sensorimotor circuit neurodegeneration - Liang, Chun-Chi (American Society for Clinical Investigation, 2014)
Lack of a preclinical model of primary dystonia that exhibits dystonic-like twisting movements has stymied identification of the cellular and molecular underpinnings of the disease. The classical familial form of primary dystonia is caused by the DYT1 (ΔE) mutation in TOR1A, which encodes torsinA, AAA(+) ATPase resident in the lumen of the endoplasmic reticular/nuclear envelope. Here, we found that conditional deletion of Tor1a in the CNS (nestin-Cre Tor1a(flox/–)) or isolated CNS expression of DYT1 mutant torsinA (nestin-Cre Tor1a(flox/ΔE)) causes striking abnormal twisting movements. These animals developed perinuclear accumulation of ubiquitin and the E3 ubiquitin ligase HRD1 in discrete sensorimotor regions, followed by neurodegeneration that was substantially milder in nestin-Cre Tor1a(flox/ΔE) compared with nestin-Cre Tor1a(flox/–) animals. Similar to the neurodevelopmental onset of DYT1 dystonia in humans, the behavioral and histopathological abnormalities emerged and became fixed during CNS maturation in the murine models. Our results establish a genetic model of primary dystonia that is overtly symptomatic, and link torsinA hypofunction to neurodegeneration and abnormal twisting movements. These findings provide a cellular and molecular framework for how impaired torsinA function selectively disrupts neural circuits and raise the possibility that discrete foci of neurodegeneration may contribute to the pathogenesis of DYT1 dystonia.